MiR-199a-5p–HIF-1α-STAT3 Positive Feedback Loop Contributes to the Progression of Non-Small Cell Lung Cancer - Yang, Xingping; Zheng, Yuzhen; Tan, Jian; Tian, Renjiang; Shen, Piao; Cai, Weijie; Liao, Hongying (Frontiers in Cell and Developmental Biology, 2021)
Background: Non-small cell lung cancer (NSCLC) is the most common malignancy worldwide. MiR-199a-5p has been reported to play important roles in multiple tumors, inclusive of NSCLC. Whereas, little is definitively known pertaining to its explicit mechanism of action in NSCLC. Methods: Expression of miR-199a-5p and HIF-1α mRNA were quantified employing qRT-PCR. H1299 and A549 cells were transiently transfected with miR-199a-5p mimics or inhibitors. Then CCK-8 assays, flow cytometry analysis, Transwell assay were performed for detecting cell proliferation, cell cycle, apoptosis, migration and invasion of NSCLC cells, respectively. HIF-1α, STAT3 and p-STAT3 expression were detected via Western blotting. Bioinformatic analysis and dual-luciferase assay were performed for investigating the interactions among miR-199a-5p, HIF-1α and STAT3. Xenograft models were established with nude mice for further analyzing the Bevacizumab resistance of NSCLC cells. Results: MiR-199a-5p expression was markedly attenuated in NSCLC tissues and cell lines. Overexpression of miR-199a-5p repressed the proliferation, migration, invasion but induced apoptosis of NSCLC cells. HIF-1α was identified as a direct target of miR-199a-5p. There was a positive feed-back loop between miR-199a-5p, HIF-1α and STAT3. Co-transfection of HIF-1α or STAT3 overexpression plasmids counteracted effects of miR-199a-5p. In vivo experiments indicated that the feed-back loop was in association with the Bevacizumab resistance of NSCLC cells . Conclusion: MiR-199a-5p blocked the progression of NSCLC and sensitized NSCLC cells to Bevacizumab by suppressing HIF-1α and STAT3, while HIF-1α/STAT3 axis suppressed the expression of miR-199a-5p, which forms a positive feed-back loop to promote the sustaining progression of NSCLC.